2018
DOI: 10.1002/cctc.201801220
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Two‐Step Hydrolysis of Nerve Agents by a Nanozyme

Abstract: Organophosphate‐based nerve agents irreversibly inhibit acetylcholinesterase enzyme, leading to respiratory failure, paralysis and death. Several organophosphorus hydrolases are capable of degrading nerve agents including pesticides and insecticides. Development of stable artificial enzymes capable of hydrolysing nerve agents is important for the degradation of environmentally toxic organophosphates. Herein, we describe a Zr‐incorporated CeO2 nanocatalyst that can be used for an efficient capture and hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
4
20
0
Order By: Relevance
“…Additionally, there are few hydrolytic nanozymes reported to hydrolyze the toxic biological agents such as neurotoxic organophosphates. In an attempt, Khulbe et al (2018) showed the development of Zr-incorporated CeO 2 nanocatalyst for efficient hydrolysis of nerve agents such as methyl paraoxon to less toxic monoesters. It was a first report showing a nanozymes catalyzing a two-step hydrolysis reaction with a faster catalytic rate (t 1/2 value of 1.2 and 3.5 min for methyl paraoxon and methyl parathion hydrolysis, respectively) than the single-step hydrolysis reaction reported earlier by others.…”
Section: Antioxidant Nanozymesmentioning
confidence: 99%
“…Additionally, there are few hydrolytic nanozymes reported to hydrolyze the toxic biological agents such as neurotoxic organophosphates. In an attempt, Khulbe et al (2018) showed the development of Zr-incorporated CeO 2 nanocatalyst for efficient hydrolysis of nerve agents such as methyl paraoxon to less toxic monoesters. It was a first report showing a nanozymes catalyzing a two-step hydrolysis reaction with a faster catalytic rate (t 1/2 value of 1.2 and 3.5 min for methyl paraoxon and methyl parathion hydrolysis, respectively) than the single-step hydrolysis reaction reported earlier by others.…”
Section: Antioxidant Nanozymesmentioning
confidence: 99%
“…In biosystems, the cleavage of phosphoester bonds is accomplished by a family of enzymes called phosphohydrolase via a catalytic hydrolysis manner (Figure a). Because the fragile structures of enzymes limit their applications in complex conditions and increase the costs of storage and transportation, scientists have been struggling to develop stable catalysts as substitutes of phosphohydrolase to cut phosphoester bonds. Recently, the development of such catalysts based on nanomaterials (NMs) has been attracting particular attention owing to the high stabilities, large surface areas as well as other intriguing electronic and magnetic properties of NMs. Especially, metal-oxide NMs and metal–organic frameworks consisting of high-valent zirconium (Zr 4+ ) and cerium (Ce 4+ ) have been found to have superior activities. , Because both Zr 4+ and Ce 4+ ions are strong Lewis acids, these findings have led to the belief that a high Lewis acidity is the precondition for NMs to catalyze the hydrolysis of phosphoester bonds (Figure b). , According to such a Lewis acidity model, NMs based on noble metals, which have high stability and biocompatibility, are excluded as potential catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…pathway while later Kuchma et al [6] foundt he activity is proportional to the concentration of surface Ce 3+ .Abalanced surface Ce 4+ /Ce 3+ ratio [7] and surface oxygen vacancy [8] were also proposed the key factor facilitating this CeO 2 -catalyzed dephosphorylation. Although aw ide range of Ce-based catalysts have been reported to catalyze this reaction, [9][10][11][12] the key surface Ce species and the underlying mechanism are still unclear. Using probe-assisted nuclear magnetic resonance (NMR), we recently demonstrated that the electronic state (i.e., Lewis acidity) of surface Ce shifts "continuously" with its local structure and cannot be ascribed to the "discrete" oxidation state (e.g., 3+ and 4 + for Ce) as in literatures above.…”
Section: Introductionmentioning
confidence: 99%